The Role of Spiritually Intelligent Teachers in Fostering Holistic Student Development: An Integrative Framework - Wani, Shilpa Suresh (Journal of Educational Research and Policies, 2026)
The education system has traditionally emphasized cognitive and intellectual development, often overlooking the emotional, ethical, and spiritual dimensions essential for holistic growth. This paper explores the concept of spiritually intelligent teachers and their pivotal role in fostering holistic student development. Spiritual intelligence (SI), encompassing self-awareness, compassion, interconnectedness, and purpose, equips educators to nurture students’ intellectual, emotional, social, and moral capacities. The paper highlights theoretical frameworks, practical implications, and the integration of SI in teaching practices, underscoring its significance in shaping well-rounded, resilient, and empathetic individuals.